Environment-friendly hollow particle steel ladle heat preservation agent and preparation method thereof
By using hollow vitrified microbeads and other materials to prepare environmentally friendly hollow particle ladle insulation, the problems of dust pollution and high carbon content in the existing technology are solved, and environmentally friendly, low-density and high-efficiency insulation effects are achieved, which is suitable for the production of low-carbon steel.
Patent Information
- Application Number
- CN202510009782.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
AI Technical Summary
Existing ladle insulation agents such as carbonized rice husks have dust pollution and high carbon content, which leads to environmental pollution and increased carbon steel, making it difficult to adapt to the production of low carbon steel.
Hollow vitrified microbeads, fly ash, industrial aluminum powder, pearl sand, carbon powder and manganese oxide are used as raw materials, and granulated by mechanical stirring and disc granulator to form an environmentally friendly hollow particle ladle insulation, and the dust content is reduced through dust collector.
It achieves environmentally friendly insulation effect, reduces dust pollution, is suitable for the production of low carbon steel, and has low density, low moisture content and reduced usage.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation covering agents, and in particular to an environmentally friendly hollow particle ladle thermal insulation agent and a preparation method thereof. Background Art
[0002] For decades, Chinese steel mills have been using carbonized rice husks as heat preservation agents for ladles, tundishes and hot metal ladles. They have low density and good heat preservation effects. However, during the pouring process and when the ladle is turned over and the slag is discharged after pouring, the carbonized rice husks are scattered throughout the factory with the hot air flow, irritating the skin of operators and worsening the factory environment. In particular, carbonized rice husks drill into electrical equipment and cause equipment accidents. The high carbon content and long-term heat preservation can easily increase the carbon content of the molten steel, making it unsuitable for the production of low-carbon steel.
[0003] Patent CN117753953A discloses a riser covering agent and a preparation method thereof, and proposes a riser covering agent and a preparation method thereof comprising plant ash, sawdust, acid graphite and perlite. The mixture is stirred by a mechanical stirring method until it is evenly mixed. The covering agent and its preparation method can avoid a large amount of heat dissipation and have a good shrinkage compensation effect on the casting, effectively improve product quality, save costs, and are expected to be used and promoted in the field of castings. The disadvantage is that this method still contains a high dust content and does not fundamentally solve the problem of environmental pollution. In addition, the prepared material has a low porosity and a large bulk density. Under the premise of the same effect, the amount used is too large, and it is difficult to use and promote it as a ladle insulation agent in steelmaking enterprises.
[0004] Based on this, the present invention provides an environmentally friendly hollow particle ladle insulation agent and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide an environmentally friendly hollow particle ladle insulation agent and a preparation method thereof, which can not only improve the insulation effect, but also solve the environmental problems caused by dust.
[0006] On the one hand, the present invention provides an environmentally friendly hollow particle ladle insulation agent, which is prepared from the following raw materials in parts by weight: 10-20 parts of hollow vitrified microspheres, 35-55 parts of fly ash, 5-20 parts of industrial aluminum powder, 0-15 parts of pearl sand, 10-15 parts of carbon powder, and 1-3 parts of a trigger.
[0007] Furthermore, the thermal insulation agent is prepared from the following raw materials in parts by weight: 15 parts of hollow vitrified microspheres, 48 parts of fly ash, 8 parts of industrial aluminum powder, 12 parts of pearl sand, 15 parts of carbon powder, and 2 parts of triggering agent.
[0008] Furthermore, the particle size of the vitrified microspheres is 1-3 mm, and the middle part is a closed hollow particle.
[0009] Hollow vitrified microspheres are solid microbubbles with a vitrified surface and closed interior. This structure requires heat to pass through more air layers during the transfer process, thereby increasing the resistance to heat conduction and reducing the thermal conductivity. At the same time, the lightweight characteristics of hollow vitrified microspheres also reduce the overall weight of the insulation, making it easier to construct and transport.
[0010] After being processed, fly ash can be used as an additive for thermal insulation materials. Its granular structure forms a porous structure in the thermal insulation agent, which is beneficial to reduce the thermal bridge effect and improve the thermal insulation effect. The silicate and other components in fly ash also play a role in thermal insulation to a certain extent.
[0011] Industrial aluminum powder plays a major role in heat preservation. Due to its metallic luster and high reflectivity, it can effectively reflect heat back and reduce heat absorption and transfer. At the same time, the addition of aluminum powder also improves the strength and durability of the insulation.
[0012] The addition of pearl sand further increases the porosity and lightness of the insulation. Its particle shape and size are evenly distributed, which is conducive to forming a more compact and stable insulation layer. The thermal insulation properties of pearl sand also help to reduce thermal conductivity.
[0013] The carbon powder burns and generates heat when it meets the molten steel, thus reheating the molten steel on the surface of the ladle. Although its own thermal insulation performance is limited, it can further improve the heating and thermal insulation performance of the thermal insulation agent when it works in synergy with other ingredients.
[0014] Furthermore, the particle size of the pearl sand is 16-30 mesh.
[0015] Furthermore, the particle size of the carbon powder is 40-100 meshes.
[0016] Furthermore, the triggering agent is manganese oxide. In addition to accelerating the ignition time, the addition of manganese oxide can also significantly reduce the viscosity of the slag.
[0017] On the other hand, the present invention also provides a method for preparing an environmentally friendly hollow particle ladle insulation agent, the steps comprising: breaking and grinding pearl sand and carbon powder respectively as required to meet the particle requirements; weighing hollow vitrified microspheres, fly ash, industrial aluminum powder, pearl sand, carbon powder and triggering agent according to weight ratio; adding water and adhesive for stirring, and stirring the mixture by a mechanical stirring method until it is evenly mixed; granulating by a disc granulator, during the rotation process, the raw material powder adheres to the surface of pearl sand and vitrified microspheres to form nuclei; the resulting balls are distributed and dried by a distribution machine, and after drying, the dust on the surface of the particles is removed by a primary dust remover to reduce dust during on-site use; finally, screening and packaging are performed, and abnormally large particles (greater than 8mm) and tiny particles less than 0.2mm are removed in the screening process, and the particles after screening are packaged and stored, and secondary dust removal is performed during the screening process to remove dust on the surface of the particles to reduce dust during on-site use.
[0018] Furthermore, the equipment used in the grinding step is a grinder, and the equipment used in the breaking step is a cone crusher.
[0019] Furthermore, the rotation speed of the mechanical stirring is 80-200 r / min, the mechanical stirring time is 18-25 min, and the proportion of water added is 25-40% of the weight of the raw materials.
[0020] Furthermore, the binder comprises modified carboxymethyl cellulose and CaO powder in a weight ratio of (3-4):1, and the addition ratio is 3-5% of the weight of the raw materials.
[0021] Furthermore, the preparation method of the modified carboxymethyl cellulose includes: weighing carboxymethyl cellulose and dispersing it in water to obtain a carboxymethyl cellulose solution; dispersing corn starch in water, heating it to a temperature of 75-85°C, and adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 75-85°C, continuing to stir for 60-70 minutes, cooling the mixture to room temperature, filtering, washing and drying.
[0022] Furthermore, the weight ratio of carboxymethyl cellulose to water in the carboxymethyl cellulose solution is (4.5-5.5) g:100 mL.
[0023] Furthermore, when the corn starch is dispersed in water, the weight ratio of corn starch to water is (4.5-5.5) g:30 mL.
[0024] The beneficial effects of the present invention are: The present invention utilizes vitrified microsphere particles (with a closed hollow in the middle) to rotate under the action of the centrifugal force of a ball-making disk, and raw material powder adheres to the surface of the microsphere particles to form nuclei, which are then sent into the ball-forming disk. After the microsphere nuclei enter the ball-forming disk, they are affected by the centrifugal force, friction force and gravity in the disk, move along a parabola, and continuously squeeze the moisture in the microspheres out of the surface during the continuous rolling process, so that the resulting microspheres have certain strength, less dust, low water content, low density and good thermal insulation effect.
[0025] Modified carboxymethyl cellulose and CaO powder are used as composite binders in the present invention. Carboxymethyl cellulose is modified by starch, and plays a role in connecting and fixing various components in the thermal insulation agent, and hollow vitrified microspheres, fly ash, industrial aluminum powder and other raw materials are tightly combined together to form a stable porous structure. This porous structure is conducive to reducing the thermal bridge effect, that is, heat needs to pass through more air layers or solid layers during the transfer process, thereby increasing the resistance of heat conduction and reducing the thermal conductivity. The raw materials such as hollow vitrified microspheres, fly ash, industrial aluminum powder themselves have a low thermal conductivity and good thermal insulation performance. After they are combined with binders such as modified carboxymethyl cellulose and CaO powder, a more compact and stable porous structure can be formed, further improving the thermal insulation effect of the thermal insulation agent.
[0026] Among them, modified carboxymethyl cellulose is obtained by adding additives such as corn starch to carboxymethyl cellulose. This modification makes carboxymethyl cellulose have better dispersibility, stability and adhesion. The functional groups such as hydroxyl and carboxyl in the modified carboxymethyl cellulose molecules can chemically react or physically adsorb with inorganic substances such as CaO powder to form a stronger chemical bond or physical connection. At the same time, the modified carboxymethyl cellulose also has a certain water retention performance, which can maintain a certain humidity during the preparation process, which is conducive to the uniform mixing and close bonding between the components.
[0027] As an alkaline substance, CaO powder can react with the acidic functional groups in modified carboxymethyl cellulose to generate corresponding salt compounds. This reaction not only helps to enhance the bonding properties of the binder, but also improves the stability and durability of the thermal insulation agent. In addition, CaO powder can also react with carbon dioxide in the air to generate compounds such as calcium carbonate, further increasing the hardness and strength of the thermal insulation agent.
[0028] The environmentally friendly hollow particle ladle heat preservation agent and preparation method provided by the present invention have the effect of expansion and heat preservation after preheating of the hollow particle glass microspheres in the components, thereby preventing the heat from being lost too quickly; by adding carbon powder, the carbon powder burns and generates heat after encountering molten steel, thereby heating the molten steel on the surface of the ladle for the second time; in addition, after the pearl sand is preheated and expanded, the volume rapidly expands to form an insulation layer, thereby improving the good heat preservation performance. Fly ash powder has a low thermal conductivity and can be used as a heat preservation material, and alumina plays a role in regulating fluidity. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that the trigger in the present invention is manganese oxide. Example 1
[0030] This embodiment provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: Pearl sand and carbon powder are broken and ground as required, wherein the mesh number of the pearl sand is 20 and the particle size of the carbon powder is 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, industrial aluminum powder, pearl sand, carbon powder, and triggering agent in weight ratios of 15 parts, 48 parts, 8 parts, 12 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; The binder comprises modified carboxymethyl cellulose and CaO powder in a weight ratio of 3.5:1, and the addition ratio is 4% of the weight of the raw materials; the preparation method of the modified carboxymethyl cellulose comprises: weighing 5g of carboxymethyl cellulose and dispersing it in 100mL of water to obtain a carboxymethyl cellulose solution; dispersing 5g of corn starch in 30mL of water, heating to 80°C, adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 80°C, continuing to stir for 65 minutes, cooling the mixture to room temperature, filtering, washing and drying to obtain the obtained product; S4: Granulate through a disc granulator with a disc diameter of 1500mm. During the rotation process, the raw material powder adheres to the surface of pearl sand and vitrified microspheres to form nuclei. The rotation speed is 22r / min.
[0031] S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0032] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 6mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-6mm and a bulk density of less than 920g / dm 3 , water content ≤3%. Example 2
[0033] This embodiment provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: Pearl sand and carbon powder are broken and ground as required, wherein the mesh number of the pearl sand is 20 and the particle size of the carbon powder is 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, industrial aluminum powder, pearl sand, carbon powder, and triggering agent in weight ratios of 15 parts, 50 parts, 8 parts, 10 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; The binder comprises modified carboxymethyl cellulose and CaO powder in a weight ratio of 3.5:1, and the addition ratio is 4% of the weight of the raw materials; the preparation method of the modified carboxymethyl cellulose comprises: weighing 5g of carboxymethyl cellulose and dispersing it in 100mL of water to obtain a carboxymethyl cellulose solution; dispersing 5g of corn starch in 30mL of water, heating to 80°C, adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 80°C, continuing to stir for 65 minutes, cooling the mixture to room temperature, filtering, washing and drying to obtain the obtained product; S4: Granulate through a disc granulator with a disc diameter of 1500mm. During the rotation process, the raw material powder adheres to the surface of pearl sand and vitrified microspheres to form nuclei. The rotation speed is 22r / min.
[0034] S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0035] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 6mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-6mm and a bulk density of less than 900g / dm 3 , water content ≤3%. Example 3
[0036] This embodiment provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: The carbon powder is ground as required, wherein the pearl sand has a mesh number of 20 and the carbon powder has a particle size of 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, industrial aluminum powder, carbon powder, and triggering agent in weight ratios of 15 parts, 55 parts, 13 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and the mixture is stirred by a mechanical stirring method, the stirring speed is 150r / min, and the stirring time is 20min, until the mixture is uniformly mixed; The binder comprises modified carboxymethyl cellulose and CaO powder in a weight ratio of 3.5:1, and the addition ratio is 5% of the weight of the raw materials; the preparation method of the modified carboxymethyl cellulose comprises: weighing 5g of carboxymethyl cellulose and dispersing it in 100mL of water to obtain a carboxymethyl cellulose solution; dispersing 5g of corn starch in 30mL of water, heating to 80°C, adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 80°C, continuing to stir for 65 minutes, cooling the mixture to room temperature, filtering, washing and drying to obtain the obtained product; S4: Granulate through a disc granulator with a disc diameter of 2500mm. During the rotation process, the raw material powder adheres to the surface of the glass microspheres to form nuclei. The rotation speed is 18r / min. S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0037] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 8mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-8mm and a bulk density of less than 850g / dm 3 , water content ≤2.5%. Example 4
[0038] This embodiment provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: The carbon powder is ground as required, wherein the pearl sand has a mesh number of 20 and the carbon powder has a particle size of 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, industrial aluminum powder, carbon powder, and triggering agent in weight ratios of 15 parts, 48 parts, 20 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; The binder comprises modified carboxymethyl cellulose and CaO powder in a weight ratio of 3:1, and the addition ratio is 5% of the weight of the raw materials; the preparation method of the modified carboxymethyl cellulose comprises: weighing 5g of carboxymethyl cellulose and dispersing it in 100mL of water to obtain a carboxymethyl cellulose solution; dispersing 5g of corn starch in 30mL of water, heating to 80°C, and adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 80°C, continuing to stir for 65 minutes, cooling the mixture to room temperature, filtering, washing and drying to obtain the obtained product; S4: Granulate through a disc granulator with a disc diameter of DN2000. During the rotation process, the raw material powder adheres to the surface of the glass microspheres to form nuclei. The rotation speed is 18r / min. S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 300°C and the drying time is 3 hours.
[0039] S6: Screening and packaging. During the screening process, abnormally large particles (greater than 5mm) and tiny particles less than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-5mm, ≤950g / dm 3 , water content ≤3.5%.
[0040] Comparative Example 1 This comparative example provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: Pearl sand and carbon powder are broken and ground as required, wherein the mesh number of the pearl sand is 20 and the particle size of the carbon powder is 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, industrial aluminum powder, pearl sand, carbon powder, and triggering agent in weight ratios of 15 parts, 48 parts, 8 parts, 12 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; The binder includes carboxymethyl cellulose and CaO powder in a weight ratio of 3.5:1, and the addition ratio is 4% of the weight of the raw materials; S4: Granulate through a disc granulator with a disc diameter of 1500mm. During the rotation process, the raw material powder adheres to the surface of pearl sand and vitrified microspheres to form nuclei. The rotation speed is 22r / min.
[0041] S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0042] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 6mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-6mm and a bulk density of less than 920g / dm 3 , water content ≤3%.
[0043] Comparative Example 2 This comparative example provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: Pearl sand and carbon powder are broken and ground as required, wherein the mesh number of the pearl sand is 20 and the particle size of the carbon powder is 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, industrial aluminum powder, pearl sand, carbon powder, and triggering agent in weight ratios of 15 parts, 48 parts, 8 parts, 12 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; Among them, the binder is CaO powder, and the addition ratio is 4% of the raw material weight; S4: granulation is carried out by a disc granulator with a disc diameter of 1500mm. During the rotation process, the raw material powder adheres to the surface of pearl sand and vitrified microspheres to form nuclei, and the rotation speed is 22r / min.
[0044] S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0045] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 6mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-6mm and a bulk density of less than 920g / dm 3 , water content ≤3%.
[0046] Comparative Example 3 This comparative example provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: Pearl sand and carbon powder are broken and ground as required, wherein the mesh number of the pearl sand is 20 and the particle size of the carbon powder is 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, industrial aluminum powder, pearl sand, carbon powder, and triggering agent in weight ratios of 15 parts, 48 parts, 8 parts, 12 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; The binder is modified carboxymethyl cellulose, and the addition ratio is 4% of the weight of the raw material; the preparation method of modified carboxymethyl cellulose includes: weighing 5g of carboxymethyl cellulose and dispersing it into 100mL of water to obtain a carboxymethyl cellulose solution; dispersing 5g of corn starch into 30mL of water, heating to 80°C, and adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 80°C, continuing to stir for 65 minutes, cooling the mixture to room temperature, filtering, washing and drying to obtain the obtained product; S4: Granulate through a disc granulator with a disc diameter of 1500mm. During the rotation process, the raw material powder adheres to the surface of pearl sand and vitrified microspheres to form nuclei. The rotation speed is 22r / min.
[0047] S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0048] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 6mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-6mm and a bulk density of less than 920g / dm 3 , water content ≤3%.
[0049] Comparative Example 4 This comparative example provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: Pearl sand and carbon powder are broken and ground as required, wherein the mesh number of the pearl sand is 20 and the particle size of the carbon powder is 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, industrial aluminum powder, pearl sand, carbon powder, and triggering agent in weight ratios of 15 parts, 48 parts, 8 parts, 12 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; Wherein, the binder is carboxymethyl cellulose; S4: Granulate through a disc granulator with a disc diameter of 1500mm. During the rotation process, the raw material powder adheres to the surface of pearl sand and vitrified microspheres to form nuclei. The rotation speed is 22r / min.
[0050] S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0051] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 6mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-6mm and a bulk density of less than 920g / dm 3 , water content ≤3%.
[0052] Comparative Example 5 This comparative example provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: Pearl sand and carbon powder are broken and ground as required, wherein the mesh number of the pearl sand is 20 and the particle size of the carbon powder is 90 mesh; S2: Raw materials include: fly ash, industrial aluminum powder, pearl sand, carbon powder, and triggering agent in weight ratios of 48 parts, 8 parts, 12 parts, 15 parts, and 2 parts respectively; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; The binder comprises modified carboxymethyl cellulose and CaO powder in a weight ratio of 3.5:1, and the addition ratio is 4% of the weight of the raw materials; the preparation method of the modified carboxymethyl cellulose comprises: weighing 5g of carboxymethyl cellulose and dispersing it in 100mL of water to obtain a carboxymethyl cellulose solution; dispersing 5g of corn starch in 30mL of water, heating to 80°C, adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 80°C, continuing to stir for 65 minutes, cooling the mixture to room temperature, filtering, washing and drying to obtain the obtained product; S4: Granulate through a disc granulator with a disc diameter of 1500mm. During the rotation process, the raw material powder adheres to the surface of the pearl sand to form nuclei, and the rotation speed is 22r / min.
[0053] S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0054] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 6mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a particle size of 0.2-6mm with a bulk density of less than 920g / dm 3 , water content ≤3%.
[0055] Comparative Example 6 This comparative example provides an environmentally friendly hollow particle ladle insulation agent, including the following preparation method: S1: Pearl sand and carbon powder are broken and ground as required, wherein the mesh number of the pearl sand is 20 and the particle size of the carbon powder is 90 mesh; S2: The raw materials include: hollow vitrified microspheres, fly ash, pearl sand, carbon powder, and triggering agent in weight ratios of 15 parts, 48 parts, 12 parts, 15 parts, and 2 parts respectively; the particle size of the hollow vitrified microspheres is 2 mm; S3: adding water and adhesive to stir, the proportion of water added is 30% of the weight of the raw material, and stirring the mixture by mechanical stirring method, the stirring speed is 200r / min, and the stirring time is 20min, until the mixture is uniformly mixed; The binder comprises modified carboxymethyl cellulose and CaO powder in a weight ratio of 3.5:1, and the addition ratio is 4% of the weight of the raw materials; the preparation method of the modified carboxymethyl cellulose comprises: weighing 5g of carboxymethyl cellulose and dispersing it in 100mL of water to obtain a carboxymethyl cellulose solution; dispersing 5g of corn starch in 30mL of water, heating to 80°C, adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 80°C, continuing to stir for 65 minutes, cooling the mixture to room temperature, filtering, washing and drying to obtain the obtained product; S4: Granulate through a disc granulator with a disc diameter of 1500mm. During the rotation process, the raw material powder adheres to the surface of pearl sand and vitrified microspheres to form nuclei. The rotation speed is 22r / min.
[0056] S5: Spreading and drying. The resulting balls are spread and dried by a spreading machine. After drying, the dust on the surface of the particles is removed by a dust collector to reduce dust during on-site use. The drying temperature is 200°C and the drying time is 4 hours.
[0057] S6: Screening and packaging. During the screening process, abnormally large particles (larger than 6mm) and tiny particles smaller than 0.2mm are removed. After screening, the particles are packaged and stored. The product is a hollow particle with a specification of 0.2-6mm and a bulk density of less than 920g / dm 3 , water content ≤3%.
[0058] Test Example: The thermal conductivity and molten iron temperature drop performance tests were performed on the thermal insulation agents prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-6. The test results are shown in Table 1: Table 1
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. An environmentally friendly hollow particle ladle insulation agent, characterized in that: The invention is prepared from the following raw materials in parts by weight: 10-20 parts of hollow vitrified microspheres, 35-55 parts of fly ash, 5-20 parts of industrial aluminum powder, 0-15 parts of pearl sand, 10-15 parts of carbon powder and 1-3 parts of a trigger.
2. The environmentally friendly hollow particle ladle insulation agent according to claim 1, characterized in that: The heat preservation agent is prepared from the following raw materials in parts by weight: 15 parts of hollow vitrified microspheres, 48 parts of fly ash, 8 parts of industrial aluminum powder, 12 parts of pearl sand, 15 parts of carbon powder, and 2 parts of triggering agent.
3. The environmentally friendly hollow particle ladle insulation agent according to claim 1, characterized in that: The particle size of the vitrified microspheres is 1-3 mm, and the middle part is a closed hollow particle.
4. The environmentally friendly hollow particle ladle insulation agent according to claim 1, characterized in that: The particle size of the pearl sand is 16-30 meshes, and the particle size of the carbon powder is 40-100 meshes.
5. The environmentally friendly hollow particle ladle insulation agent according to claim 1, characterized in that: The trigger is manganese oxide.
6. A method for preparing the environmentally friendly hollow particle ladle insulation agent according to any one of claims 1 to 5, characterized in that the steps include: The pearl sand and carbon powder are broken and ground respectively as required to achieve the particle size requirements; The hollow vitrified microspheres, fly ash, industrial aluminum powder, pearl sand, carbon powder and a trigger are weighed according to weight ratio; water and a binder are added for stirring, and the mixture is stirred by a mechanical stirring method until it is uniformly mixed; and the mixture is granulated by a disc granulator to obtain the product.
7. The method for preparing an environmentally friendly hollow particle ladle insulation agent according to claim 6, characterized in that: The rotation speed of the mechanical stirring is 80-200 r / min, the mechanical stirring time is 18-25 min, and the proportion of water added is 25-40% of the weight of the raw materials.
8. The method for preparing an environmentally friendly hollow particle ladle insulation agent according to claim 6, characterized in that: The binder comprises modified carboxymethyl cellulose and CaO powder in a weight ratio of (3-4):1, and the addition ratio is 3-5% of the weight of the raw materials.
9. The method for preparing an environmentally friendly hollow particle ladle insulation agent according to claim 8, characterized in that: The preparation method of the modified carboxymethyl cellulose comprises: weighing carboxymethyl cellulose and dispersing it in water to obtain a carboxymethyl cellulose solution; dispersing corn starch in water, heating it to a temperature of 75-85° C., adjusting the pH to 12, then adding the carboxymethyl cellulose solution, continuing to maintain the temperature at 75-85° C., continuing to stir for 60-70 minutes, cooling the mixture to room temperature, filtering, washing and drying the mixture.
10. The method for preparing an environmentally friendly hollow particle ladle insulation agent according to claim 9, characterized in that: The weight ratio of carboxymethyl cellulose to water in the carboxymethyl cellulose solution is (4.5-5.5) g:100 mL; when the corn starch is dispersed in water, the weight ratio of corn starch to water is (4.5-5.5) g:30 mL.